The power of the Mediator complex—Expanding the genetic architecture and phenotypic spectrum of MED12‐related disorders. Issue 5 (9th August 2018) - Charzewska, A.; Maiwald, R.; Kahrizi, K.; Oehl‐Jaschkowitz, B.; Dufke, A.; Lemke, J.R.; Enders, H.; Najmabadi, H.; Tzschach, A.; Hachmann, W.; Jensen, C.; Bienek, M.; et al.
Abstract : MED12 is a member of the large Mediator complex that controls cell growth, development, and differentiation. Mutations in MED12 disrupt neuronal gene expression and lead to at least three distinct X‐linked intellectual disability syndromes (FG, Lujan‐Fryns, and Ohdo). Here, we describe six families with missense variants in MED12 (p.(Arg815Gln), p.(Val954Gly), p.(Glu1091Lys), p.(Arg1295Cys), p.(Pro1371Ser), and p.(Arg1148His), the latter being first reported in affected females) associated with a continuum of symptoms rather than distinct syndromes. The variants expanded the genetic architecture and phenotypic spectrum of MED12 ‐related disorders. New clinical symptoms included brachycephaly, anteverted nares, bulbous nasal tip, prognathism, deep set eyes, and single palmar crease. We showed that MED12 variants, initially implicated in X‐linked recessive disorders in males, may predict a potential risk for phenotypic expression in females, with no correlation of the X chromosome inactivation pattern in blood cells. Molecular modeling (Yasara Structure) performed to model the functional effects of the variants strongly supported the pathogenic character of the variants examined. We showed that molecular modeling is a useful method for in silico testing of the potential functional effects of MED12 variants and thus can be a valuable addition to the interpretation of the clinical and genetic findings. Abstract :